2017
DOI: 10.1016/j.ssci.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessing a national work health and safety policy intervention using the psychosocial safety climate framework

Abstract: Despite support for work health and safety (WHS) policy interventions, the evaluation of their effectiveness has been overlooked. As such, many important policy developments have not been assessed for their impact within jurisdictions and organisations. We addressed this research gap by using the Psychosocial Safety Climate (PSC) framework, theory, measurement toolthe PSC-12, and benchmarks -to investigate the impact of a WHS policy intervention, across Australian jurisdictions, that standardised policy approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 30 publications
0
21
0
4
Order By: Relevance
“…Findings from confirmatory factor analyses support the construct validity of the theoretically based four-factor structure measured by the 12-item version of PSC (Hall et al, 2010;Pien et al, 2018). Despite the theoretical reasoning behind the PSC measure, it seems data most often are collapsed into one single composite PSC score (see e.g., Afsharian et al, 2018;Biron et al, 2018;Bronkhorst, 2015;Idris et al, 2015;Potter et al, 2017). In addition, a 4-item version comprising the theoretical dimensions has been introduced (Dollard & Bakker, 2010).…”
Section: Length and Format Of The Psc Instrumentmentioning
confidence: 83%
See 2 more Smart Citations
“…Findings from confirmatory factor analyses support the construct validity of the theoretically based four-factor structure measured by the 12-item version of PSC (Hall et al, 2010;Pien et al, 2018). Despite the theoretical reasoning behind the PSC measure, it seems data most often are collapsed into one single composite PSC score (see e.g., Afsharian et al, 2018;Biron et al, 2018;Bronkhorst, 2015;Idris et al, 2015;Potter et al, 2017). In addition, a 4-item version comprising the theoretical dimensions has been introduced (Dollard & Bakker, 2010).…”
Section: Length and Format Of The Psc Instrumentmentioning
confidence: 83%
“…A measure for PSC was first developed and introduced in Australia, where it also has been proven to be of practical relevance for policy makers and in relation to organizational interventions (Leka, Jain & Lerouge, 2017;Leka, Jain & Zwetsloot, 2010;Potter et al, 2017;Potter et al, 2019). The PSC comprises four theoretically based components: how employees perceive the senior management 1) engages, 2) prioritizes, 3) communicates, and 4) involves employees in psychosocial workplace safety issues (Dollard & Bakker, 2010).…”
Section: Psychosocial Safety Climate In Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The codes of these categories have been matched with concepts in the reviewed models by using the character 'c' in Table 2. 10 (32%) of the 31 studies found constructs included in the model and matches with categories and codes of theme 'c' (2,5,11,14,17,19,24,25,26,28). The broader organisational factors theme includes unsafe management culture and organisational impact on workers' safety categories.…”
Section: Contributing Factorsmentioning
confidence: 99%
“…Recent studies have placed importance on psychosocial conditions in policy, and demonstrated the value of workers' psychological wellbeing at work. Organisations which aim to concentrate on both physical and psychological factors together have safer working environments at lower risk of employee mental and physical health harm, and in consequence, lead to the positive workplace behaviours like work engagement and safety incident reporting [25].…”
Section: Introductionmentioning
confidence: 99%